2013
DOI: 10.1002/oby.20537
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial deformation and twist mechanics in adults with metabolic syndrome: Impact of cumulative metabolic burden

Abstract: Objective: The aim of the study is to characterize left ventricular (LV) myocardial mechanics in adults with metabolic syndrome (MetS), and elucidate the effects of multiple risk-factors on myocardial function using speckle tracking echocardiography (STE); a more sensitive method than conventional echocardiography for detecting subclinical myocardial dysfunction. Design and Methods: Cross-sectional analyses of 92 adults (50-70 years) with MetS, and 50 healthy controls included conventional echocardiography, bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
46
1
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 40 publications
9
46
1
3
Order By: Relevance
“…Our control group's fQRS percentage can be expected to be higher than that of the healthy population. Metabolic syndrome is known to be associated with deterioration in LV systolic and diastolic functions [3][4][5]. Consistent with previous studies, in our study, MetS patients had diastolic dysfunction detected by lower E velocity and E' velocity and higher A velocity, A' velocity, E/E' ratio than the non-MetS controls.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our control group's fQRS percentage can be expected to be higher than that of the healthy population. Metabolic syndrome is known to be associated with deterioration in LV systolic and diastolic functions [3][4][5]. Consistent with previous studies, in our study, MetS patients had diastolic dysfunction detected by lower E velocity and E' velocity and higher A velocity, A' velocity, E/E' ratio than the non-MetS controls.…”
Section: Discussionsupporting
confidence: 91%
“…MetS is associated with a 5-fold increase in the risk of type 2 diabetes mellitus and 2-fold risk of developing cardiovascular disease over the next 5 to 10 years [17]. MetS is known to be associated with deterioration in LV systolic and diastolic functions [3][4][5]. Myocardial fibrosis is thought to be one of the contributors to this deterioration [6,7,18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Additionally, it was reported that GLS in obese patients was significantly reduced in line with the degree of metabolic syndrome, especially in patients with central obesity. 30 Accordingly, our finding from the multivariate analysis as shown in Table 3 suggested that a reduction in GLS through obesity and progression of diabetic nephropathy led to loss of LAS-a, while aging played a role in LA compensatory regulation.…”
Section: La Strain and Gls In Stages Of Diabetic Nephropathymentioning
confidence: 75%
“…Crendal E. с соавт. [14] по-казали, что у лиц с метаболическим синдромом цент-ральное ожирение служит достоверным предиктором снижения ГПС ЛЖ. Большую жесткость миокарда ЛЖ в подгруппе пациентов с ГБ с ожирением по сравнению с пациентами без ожирения в нашем исследовании можно объяснить различными механизмами.…”
Section: Discussionunclassified